Plasma extracellular vesicle microRNAs reflecting the therapeutic effect of the CBP/β-catenin inhibitor PRI-724 in patients with liver cirrhosis - Yoshida, Mayu; Matsuzaki, Juntaro; Fujita, Koji; Kimura, Masamichi; Umezu, Tomohiro; Tokuda, Noi; Yamaguchi, Tomoko; Kuroda, Masahiko; Ochiya, Takahiro; Saito, Yoshimasa; Kimura, Kiminori (Scientific reports, 2024)
There is an unmet need for antifibrotic therapies to prevent the progression of liver cirrhosis. Previously, we conducted an exploratory trial to assess the safety and antifibrotic efficacy of PRI-724, a selective CBP/β-catenin inhibitor, in patients with liver cirrhosis. PRI-724 was well tolerated and exerted a potential antifibrotic effect. Here, we investigated whether the profiles of circulating microRNAs packaged in extracellular vesicles (EV-miRNAs) are associated with responses to liver fibrosis treatments. Eighteen patients who received PRI-724 for 12 weeks in a phase 1/2a study were classified as responders (n = 10) or non-responders (n = 8) based on changes in liver stiffness. Plasma samples were obtained before and after PRI-724 administration and the levels of EV-miRNAs were analyzed. Three miRNAs (miR-6510-5p, miR-6772-5p, and miR-4261) were identified as predictors of response or non-response to PRI-724, and the levels of three other miRNAs (miR-939-3p, miR-887-3p, and miR-7112-5p) correlated with the efficacy of treatment. Expression of miR-887-3p was detected in hepatocytes and was decreased significantly in liver tissue following PRI-724 treatment. In addition, transfection of a miR-887-3p mimic activated hepatic stellate cells. Thus, decreases in the miR-887-3p level in blood may reflect recovery from liver fibroses in patients with liver cirrhosis treated with PRI-724, although further validation studies are warranted to confirm this.